Emerging roles of extracellular vesicles in oral and maxillofacial areas - Qianting Wang; Jiayu Sun; Haci Jiang; Mengfei Yu (International Journal of Oral Science)
Abstract The oral and maxillofacial region is a highly complex area composed of multiple tissue types and bears various critical functions of the human body. Diseases in this region pose significant diagnostic and management challenges; therefore, exploring new strategies for early diagnosis, targeted treatment, and tissue reconstruction is key to improving patient prognosis and quality of life. Extracellular vesicles are a group of heterogeneous lipid-bilayer membrane structures secreted by most cell types, including exosomes, microvesicles, and apoptotic bodies. Present in various body fluids and tissues, they act as messengers via the transfer of nucleic acids, proteins, and metabolites to recipient cells. To date, studies have revealed the different roles of extracellular vesicles in physiological or pathological processes, as well as applications in disease diagnosis, prognosis, and treatment. The importance and tissue specificity of the dental and maxillofacial tissues indicate that extracellular vesicles derived from this region are promising for further research. This paper reviews the published data on extracellular vesicles derived from cells, body fluids, and tissues in oral and maxillofacial regions, summarizes the latest advances in extracellular vesicles from extensive sources, and concludes with a focus on the current research progress and application prospects of engineered exosomes in oral science.